Poor bone mineral density aggravates adjacent segment's motility compensation in patients with oblique lumbar interbody fusion with and without pedicle screw fixation: An in silico study - Huang, Chen-Yi; Zhang, Zi-Fan; Zhang, Xiao-Yu; Liu, Fei; Fang, Zhong-Xin; Xi, Zhi-Peng; Li, Jing-Chi (Frontiers in Surgery, 2022)
Objective: Motility compensation increases the risk of adjacent segment diseases (ASDs). Previous studies have demonstrated that patients with ASD have a poor bone mineral density (BMD), and changes in BMD affect the biomechanical environment of bones and tissues, possibly leading to an increase in ASD incidence. However, whether poor BMD increases the risk of ASD by aggravating the motility compensation of the adjacent segment remains unclear. The present study aimed to clarify this relationship in oblique lumbar interbody fusion (OLIF) models with different BMDs and additional fixation methods. Methods: Stand-alone (S-A) OLIF and OLIF fixed with bilateral pedicle screws (BPS) were simulated in the L4-L5 segment of our well-validated lumbosacral model. Range of motions (ROMs) and stiffness in the surgical segment and at the cranial and caudal sides’ adjacent segments were computed under flexion, extension, and unilateral bending and axial rotation loading conditions. Results: Under most loading conditions, the motility compensation of both cranial and caudal segments adjacent to the OLIF segment steeply aggravated with BMD reduction in S-A and BPS OLIF models. More severe motility compensation of the adjacent segment was observed in BPS models than in S-A models. Correspondingly, the surgical segment’s stiffness of S-A models was apparently lower than that of BPS models (S-A models showed higher ROMs and lower stiffness in the surgical segment). Conclusion: Poor BMD aggravates the motility compensation of adjacent segments after both S-A OLIF and OLIF with BPS fixation. This variation may cause a higher risk of ASD in OLIF patients with poor BMD. S-A OLIF cannot provide instant postoperative stability; therefore, the daily motions of patients with S-A OLIF should be restricted before ideal interbody fusion to avoid surgical segment complications.